2018
DOI: 10.1002/advs.201700499
|View full text |Cite
|
Sign up to set email alerts
|

3D Fabrication with Integration Molding of a Graphene Oxide/Polycaprolactone Nanoscaffold for Neurite Regeneration and Angiogenesis

Abstract: Treating peripheral nerve injury faces major challenges and may benefit from bioactive scaffolds due to the limited autograft resources. Graphene oxide (GO) has emerged as a promising nanomaterial with excellent physical and chemical properties. GO has functional groups that confer biocompatibility that is better than that of graphene. Here, GO/polycaprolactone (PCL) nanoscaffolds are fabricated using an integration molding method. The nanoscaffolds exhibit many merits, including even GO nanoparticle distribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
145
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 149 publications
(154 citation statements)
references
References 63 publications
3
145
0
Order By: Relevance
“…The noted importance of SC participation in PNI repair make SCs an attractive addition to articial nerve gras. 36 Our goals ought to evaluate the sensitivity of SCs to electrical cues in vitro that could better promote axonal growth and other related neural behaviors for PNI repair. By preparing a conductive graphenebased composite membrane with excellent electrical and mechanical property, we demonstrated that SC proliferation can be prompted through appropriate ES.…”
Section: Discussionmentioning
confidence: 99%
“…The noted importance of SC participation in PNI repair make SCs an attractive addition to articial nerve gras. 36 Our goals ought to evaluate the sensitivity of SCs to electrical cues in vitro that could better promote axonal growth and other related neural behaviors for PNI repair. By preparing a conductive graphenebased composite membrane with excellent electrical and mechanical property, we demonstrated that SC proliferation can be prompted through appropriate ES.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, here we did not observe there exist biologically synergistic recovery effect between VEGF and NGF. However, we think it may be caused by the short term recovery time we used in this study (4 weeks), as it's usually reported to last for 8 weeks or even longer for nerve recovery [8,9].…”
Section: Peripheral Sciatic Nerve Crush Injury Model and Functional Amentioning
confidence: 92%
“…Peripheral sciatic nerve crush injury model was established on Sprague Dawley (SD) rats to evaluate the therapeutic effect of PDAPEI/pDNA polyplexes. All surgical operations followed instructions in published studies [8,9,35,36]. Briefly, SD rats (weight of 150 ± 10 g) were maintained in the SPF environment for 1 week and then anesthetized by 10% chloral hydrate (0.3 mL/kg) via intraperitoneal injection.…”
Section: Peripheral Sciatic Nerve Crush Injury Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…We also discussed GO/PCL conduits via integration molding and evaluated their potential in stimulating angiogenesis to promote sciatic nerve defect repair. The possible mechanism was via vascular endothelial growth factor (VEGF) signaling 11 . Although they can effectively repair nerve injury, graphene-loaded nerve scaffolds are generally not very biocompatible, which limits their biomedical application.…”
Section: Introductionmentioning
confidence: 99%